Enhancing the mechanical properties of marine clay using cement solidification. Issue 6 (3rd July 2019) - Dahal, Bhim Kumar; Zheng, Jun-Jie; Zhang, Rong-Jun; Song, Ding-Bao
Abstract: The use of soft clay and dredged marine clays as the construction material is challenging. This is because the high water content, high compressibility and low permeability of the clay causing the instability of ground and structure. This detrimental effect of soft clay can be improved by the cement solidification process, which is relatively cheap and efficient. This paper mainly focuses on the study of improvement on the mechanical behavior of cement mixed marine clay. The soil is reconstituted by using ordinary Portland cement of 5%, 10%, 15% and 20% by its mass. The study reveals that cementation of clay significantly improves the peak and residual strength of soil. Similarly, the primary yield stress of the soil is also improved from 16 to 275 kPa as cement content increases from 5% to 20%, respectively. By using statistical tools, the relationships between various parameters are established, which are very important to define the mechanical behavior of the clay. This study reveals that the yield surface of the solidified marine clay is not a smooth elliptical surface. Rather it is composed of two linear surfaces followed by a log-linear surface which can be modeled by using simple parameters obtained from triaxial tests.